Highly Enantioselective Intermolecular Stetter Reaction of Simple Acrylates: Synthesis of a-Chiral ?-Ketoesters - Wurz, Nathalie E.; Daniliuc, Constantin G.; Glorius, Frank (Chemistry : a European journal, 2012)
Simple Stetter: A novel N-heterocyclic carbene (NHC) was designed by combining an electron-rich 2,6-dimethoxy substituent and an underestimated yet promising chiral motif. With this NHC in hand, a highly enantioselective intermolecular Stetter reaction of simple acrylates was developed, yielding versatile α-chiral γ-ketoesters. This represents the first catalytic asymmetric route towards these valuable compounds (see scheme).